Advancing knowledge and the knowledge economy - Kahin, Brian; Foray, Dominique (MIT Press, 2006)
The revolution in information technology transforms not only information and its uses but, more important, knowledge and the ways we generate and manage it. Knowledge is now seen as input, output, and capital, even if imperfectly accounted for or understood. Many businesses and public agencies are convinced that knowledge can be managed in sophisticated, rational ways and that networking and information technology are essential tools for doing so. In this collection, experts from North America and Europe look at the transformation of knowledge in the global economy in light of the rapid changes in information technology, the resulting explosion of data, the recognition of intangibles as sources of value and liability, and the increasingly blurred distinction between private and public knowledge. The appeal of the Internet as boundary-spanning knowledge infrastructure, bridging all sectors of the economy, is shadowed by another infrastructure of rights-based contracts, practices, and institutions. The contributors address the ways in which the processes for creating and organizing knowledge interact with information technology, business strategy, and changing social and economic conditions. They discuss the balkanization that results from the complexity of the knowledge economy, the variety of knowledge resources, the great diversity of institutional and market contexts, and competing models of control and cooperation--and of proprietary and non-proprietary knowledge. ContributorsBerglind Asgeirsdottir, Carliss Y. Baldwin, Kim B. Clark, Iain M. Cockburn, Patrick Cohendet, Robin Cowan, Paul A. David, Jan Fagerberg, Brian Fitzgerald, Dominque Foray, Peter A. Freeman, Fred Gault, Dietmar Harhoff, Margaret Hedstrom, C. Suzanne Iacono, Brian Kahin, John Leslie King, Kurt Larsen, Josh Lerner, Bengt-Ake Lundvall, David C. Mowery, Arti K. Rai, Bhaven Sampat, Martin Schaaper, Tom Schuller, W. Edward Steinmueller, Stefan Thomke, Jean Tirole, Reinhilde Veugelers, Stephan Vincent-Lancrin, Eric von Hippel, Andrew Wyckoff